Effects of Lower Limbs Stretching on the Neck Range of Motion: Preliminary Evidence for Myofascial Sequence? - Calgaro, Jenny; Bonaldi, Lorenza; Sposta, Simona Mrakic; Fede, Caterina; Stecco, Antonio; Pirri, Carmelo; Stecco, Carla (International Journal of Orthopedics and Rehabilitation, 2023)
In recent years, various studies have demonstrated that the fascia can transmit the mechanical tensions generated by muscle activity over a distance. However, it is not yet clear whether this transmission follows precise anatomical lines. The present study aims to understand if the exercises at a distance can influence the range of motion of the neck, and if the effects are different by performing the exercises in various directions. The study was attended by 30 healthy volunteers aged between 19 and 32 years. Anterior flexion of the neck was checked before the protocols and retested to compare the difference after stretching the hamstrings and adductors. All evaluations were performed by the same operator using an electronic goniometer. Cervical ROM increased during both procedures, but after the hamstrings stretch it increased significantly more than after the adductors stretch (6.22° versus 1.44°). This study highlighted how fascia can transmit forces at a distance, but only according to precise myofascial sequences. Consequently, it is important to know the fascial organization in order to properly train the fascial system.